Course Review Horay, Explanation, and Critical Thinking Skills: Their Interaction Effect on EFL Learners’ Grammar Competence - Mukminatus Zuhriyah; Maskhurin Fajarina (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2021)
The purpose of this study was to look at whether or not there was an interaction effect among CRH, the explanation, and the students’ CTS implementation toward the learners’ grammar competence. The sample of this factorial 2x2 study was the second-semester students of two non-English department classes of education faculty of a university in Jombang. The instruments used were an argumentative essay test for classifying the students’ CTS and the grammar test for measuring their grammar competence in CRH and the explanation classes. The sstudents’ grammar scores from both classes were analyzed using ANOVA and TUKEY tests. The results showed that CRH, the explanation, and the students’ CTS had an interaction effect on the EFL learners’ grammar competence.